2019
DOI: 10.1080/14686996.2019.1655664
|View full text |Cite
|
Sign up to set email alerts
|

Ca–Ag compounds in ethylene epoxidation reaction

Abstract: The ethylene epoxidation is a challenging catalytic process, and development of active and selective catalyst requires profound understanding of its chemical behaviour under reaction conditions. The systematic study on intermetallic compounds in the Ca-Ag system under ethylene epoxidation conditions clearly shows that the character of the oxidation processes on the surface originates from the atomic interactions in the pristine compound. The Ag-rich compounds Ca 2 Ag 7 and CaAg 2 undergo oxidation towards fcc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 95 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…While this cannot be explained by the chemical potential, quantum chemical calculations showed that the strong adsorption of ethylene on the intermetallic surfaces hinders oxidation, thus stabilising the surface against the reactive atmosphere. As expected, this behaviour is not isotropic and a contribution gives all the details of this interesting interplay[ 123 ].…”
Section: Addressing Catalytic Challengesmentioning
confidence: 64%
“…While this cannot be explained by the chemical potential, quantum chemical calculations showed that the strong adsorption of ethylene on the intermetallic surfaces hinders oxidation, thus stabilising the surface against the reactive atmosphere. As expected, this behaviour is not isotropic and a contribution gives all the details of this interesting interplay[ 123 ].…”
Section: Addressing Catalytic Challengesmentioning
confidence: 64%
“…For example, for Pd 3 Zr, the surface Zr no longer retains its metallic state, even in the presence of parts per billion levels of oxygen . In this context, it is generally difficult to use alloys containing alkali or alkaline-earth metals as catalysts while retaining their surfaces in their original metallic state.…”
Section: Classificationmentioning
confidence: 99%
“…In previous studies, intermetallic CaAg 2 was reportedly an attractive catalyst in ethylene epoxidation. 30 Therefore, we expected to obtain valuable insights regarding catalytic applicability from the prepared CaPt 2 catalysts. A commercial carbon catalyst with 3 wt% Pt was used as a reference catalyst to evaluate the alloying effect of Pt with Ca on hydrogenation performance.…”
mentioning
confidence: 99%